Pengaruh Faktor Potensial Terhadap Tingkat Depresi Pada Dokter Peserta Program Pendidikan Dokter Spesialis (PPDS) di Indonesia - Fahri Husaini Alkaf (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The Ministry of Health released screening data on the depression levels of doctors in the Specialist Doctor Education Program (PPDS) at Vertical Teaching Hospitals, showing that 22.4% of PPDS doctors experience depression and up to 0.3% have suicidal thoughts. This study aims to analyze the influence of the work environment on depression levels among PPDS doctors in Indonesia. Depression is one of the mental health issues often faced by PPDS doctors due to high workloads, academic pressure, and lack of social support. Using a normative juridical research method, this study examines the regulations and policies governing the work environment and their impact on the mental health of PPDS doctors. The results indicate that an unconducive work environment significantly contributes to increased depression levels among PPDS doctors. Efforts to improve the work environment through more responsive policies and adequate mental health support are necessary to reduce depression levels